Receptive Vocabulary of Children With Bilateral Cochlear Implants From 3 to 16 Years of Age. Issue 6 (15th April 2022) - Busch, Tobias; Brinchmann, Ellen Irén; Braeken, Johan; Wie, Ona Bø
Abstract : Objectives: The vocabulary of children with cochlear implants is often smaller than that of their peers with typical hearing, but there is uncertainty regarding the extent of the differences and potential risks and protective factors. Some studies indicate that their receptive vocabulary develops well at first, but that they fail to keep up with their typical hearing peers, causing many CI users to enter school with a receptive vocabulary that is not age-appropriate. To better understand the receptive vocabulary abilities of children with cochlear implants this study explored age-related differences to matched children with typical hearing and associations between vocabulary skills and child-level characteristics. Design: A retrospective cross-sectional study with matched controls was conducted at the Norwegian national cochlear implant center at Oslo University Hospital. Eighty-eight children (mean age 8.7 years; range 3.2 to 15.9; 43 girls, 45 boys) who had received bilateral cochlear implants before 3 years of age were compared with two groups of children with typical hearing. One group was matched for maternal education, sex, and chronological age, the other group was matched for maternal education, sex, and hearing age. Receptive vocabulary performance was measured with the British Picture Vocabulary Scale. Results: Cochlear implant users' receptive vocabulary was poorer than that of age-matched children with typical hearing ( M = 84.6 standard points, SD = 21.1; children with typical hearing: M = 102.1 standard points, SD = 15.8; mean difference −17.5 standard points, 95% CI [−23.0 to −12.0], p < 0.001; Hedges's g = −0.94, 95% CI [−1.24 to −0.62]), and children with cochlear implants were significantly more likely to perform below the normative range (risk ratio = 2.2, 95% CI [1.42 to 3.83]). However, there was a significant nonlinear U-shaped effect of age on the scores of cochlear implant users, with the difference to the matched typical hearing children being largest (23.9 standard points, on average) around 8.7 years of age and smaller toward the beginning and end of the age range. There was no significant difference compared with children with typical hearing when differences in auditory experience were accounted for. Variability was not significantly different between the groups. Further analysis with a random forest revealed that, in addition to chronological age and hearing age, simultaneous versus sequential implantation, communication mode at school, and social integration were predictors of cochlear implant users' receptive vocabulary. Conclusions: On average, the receptive vocabulary of children with cochlear implants was smaller than that of their typical hearing peers. The magnitude of the difference was changing with age and was the largest for children in early primary school. The nonlinear effect of age might explain some of the ambiguity in previous research findings and could indicate that better intervention is required around school entry. The results emphasize that continuous monitoring and support are crucial to avoid far-reaching negative effects on the children's development and well-being.